Cyclic Alkenylsulfonyl Fluorides: Palladium‐Catalyzed Synthesis and Functionalization of Compact Multifunctional Reagents. Issue 52 (6th November 2019) - Lou, Terry Shing‐Bong; Bagley, Scott W.; Willis, Michael C.
Abstract: A series of low‐molecular‐weight, compact, and multifunctional cyclic alkenylsulfonyl fluorides were efficiently prepared from the corresponding alkenyl triflates. Palladium‐catalyzed sulfur dioxide insertion using the surrogate reagent DABSO effects sulfinate formation, before trapping with an F electrophile delivers the sulfonyl fluorides. A broad range of functional groups are tolerated, and a correspondingly large collection of derivatization reactions are possible on the products, including substitution at sulfur, conjugate addition, and N‐functionalization. Together, these attributes suggest that this method could find new applications in chemical biology. Abstract : A family of compact low‐molecular‐weight cyclic alkenylsulfonyl fluorides can be readily prepared from the corresponding alkenyl triflates using palladium catalysis. These densely functionalized reagents undergo a diverse range of derivatization reactions, including substitution at sulfur, conjugate addition, and N‐functionalization.